Romances Históricos Americanos: The Last of The Mohicans (1826), Xicoténcatl (1826) e O Guarani (1857) Configurações das Identidades Ameríndias - Lopes, Rodrigo Smaha (2015)
Several images enshrined in American History written by Europeans that not always corroborated with the reality of the time and much less with the contemporaneity were also immortalized into the romantic literature. However, the literary art sought, in many of its expressions, bring to society other images of natives not only those stereotyped ones presented in historical documents produced by the conquerors, such as those reported in the Journal of Columbus (1492) and in Caminha s Letter (1500). Within a vast number of historical novels that address the issue of characterization of the native, we decided to examine the following works: The Last of the Mohicans (1826), by James Fenimore Cooper, Xicoténcatl (1826), written anonymously and O Guarani (1857), by José de Alencar. This corpus includes settings of Amerindians from the realities of Northern Anglo-Saxon, the Spanish-American universe and also Brazil and all of them are designed within the period of American Romanticism. These works depict the figure the native and thus indicate a desire to build up American identities. Thus, we asked ourselves about what are the literary devices employed in their settings; how these settings conducted in different geocultural spaces of the continent move toward or away from each other; among others, in order to understand how romantic writers portrayed the natives during the formation of a national identity, confirming, or not, the integration of this group as part of the society. To support this work, we will use concepts of Alexis Márquez Rodríguez (1991), García Gual (2002), Mata Indurain (1995), Fernández Prieto (2003), Aínsa (1991, 2003, 2008), Trouche (2006), Fleck (2005, 2007, 2008, 2013), Lukács (1977), Milton (1992), Leenhardt (1998), Hutcheon (1991) Bernd (1998), among others that may be helpful. We hope thus enable literary scholars, specifically those who are dedicated to the reading of historical novel, by analyzing the works, a significant characterization of the natives in the romantic era, as well as strengthen the studies on the historical novel area and on comparative studies